Respuesta :
x + 2y + z = 9
x - y + 3z = 13
2z = 10
Solve the 3rd equation for z.
z = 5
Now substitute z = 5 into both the first and seconds equations.
x + 2y + 5 = 9
x - y + 3(5) = 13
x + 2y = 4
x - y = -2
Subtract the first equation from the second equation above.
-3y = -6
y = 2
Now substitute z = 5 and y = -2 into the first original equation, and solve for x.
x + 2(2) + 5 = 9
x + 9 = 9
x = 0
Answer: x = 0; y = 2; z = 5
x - y + 3z = 13
2z = 10
Solve the 3rd equation for z.
z = 5
Now substitute z = 5 into both the first and seconds equations.
x + 2y + 5 = 9
x - y + 3(5) = 13
x + 2y = 4
x - y = -2
Subtract the first equation from the second equation above.
-3y = -6
y = 2
Now substitute z = 5 and y = -2 into the first original equation, and solve for x.
x + 2(2) + 5 = 9
x + 9 = 9
x = 0
Answer: x = 0; y = 2; z = 5
2z=10
z=10/2=5 so that is easy
substitute z=5 in x-y+3z=13
x-y+3*5=13
x-y=-2
subtract x-y=-2 from x+2y+(?)=9
3y+(?)=11
if (?) is nothing, then y=11/3 or 3.67 and x=5/3 or 1.67
but if (?) is 1z, then 3y+5=11
3y=6
y=2
x=-2+y=-2+2=0
z=10/2=5 so that is easy
substitute z=5 in x-y+3z=13
x-y+3*5=13
x-y=-2
subtract x-y=-2 from x+2y+(?)=9
3y+(?)=11
if (?) is nothing, then y=11/3 or 3.67 and x=5/3 or 1.67
but if (?) is 1z, then 3y+5=11
3y=6
y=2
x=-2+y=-2+2=0